Fig. 3 in High Toxocara cati prevalence in wild, free-ranging Eurasian lynx (Lynx lynx) in Finland, 1999-2015 - Virta, Miisa; Huitu, Otso; Heikkinen, Juha; Holmala, Katja; Jokelainen, Pikka (Zenodo, 2022)
Fig. 3. Number of Toxocara cati worms in Eurasian lynx (Lynx lynx) in Finland, by age and sex. Median, first and third quartiles, and minimum and maximum are shown. Published as part of Virta, Miisa, Huitu, Otso, Heikkinen, Juha, Holmala, Katja & Jokelainen, Pikka, 2022, High Toxocara cati prevalence in wild, free-ranging Eurasian lynx (Lynx lynx) in Finland, 1999-2015, pp. 205-210 in International Journal for Parasitology: Parasites and Wildlife 17 on page 208, DOI:10.1016/j.ijppaw.2022.02.004, http://zenodo.org/record/13287925